The Portrayal of Material Culture in an Indonesian Webtoon ‘Terlalu Cantik’ - Ong, Marsha Divina (Kata Kita: Journal of Language, Literature, and Teaching, 2022)
This study uses an Indonesian Webtoon titled ‘Terlalu Cantik’ as an object of research. This Webtoon is particularly interesting as the main female character, Teh Ga, is portrayed as someone who consumes a lot of objects which differentiate her from other characters in the Webtoon, and therefore convey a message that objects carry meanings. Using material culture as a theoretical framework, this study finds out that Teh Ga utilizes different objects including means of transportation, house decoration and facilities, food, clothes, skincare products, and her social media (i.e., Instagram account) for different purposes which are to show her social status, to shape her identity, and to exercise power over others.